Sociālpedagoģiskā darbība Dubnas pagasta pašvaldībā skolēnu neattaisnoto kavējumu novēršanā - Kokina, Inita (Latvijas Universitāte, 2009)
Diplomdarbs „Sociālpedagoģiskā darbība Dubnas pagasta pašvaldībā skolēnu neattaisnoto kavējumu novēršanā” pievērš uzmanību sociāli nozīmīgai problēmai. Diplomdarba mērķis ir raksturot sociālpedagoģisko darbību Dubnas pagastā un izstrādāt darba programmu ģimenēm skolēnu neattaisnoto kavējumu novēršanā, teorētiski to pamatot un veikt šīs programmas aprobācijas rezultātu analīzi. Diplomdarbā tiek aplūkota ģimenes, skolas un sabiedrības loma skolēnu neattaisnoto kavējumu novēršanā, kā arī izvērtētas pašvaldības iespējas izglītības apguves sekmēšanā. Darba praktiskajā daļā, pamatojoties uz veikto izpēti, ir analizēti skolēnu neattaisnoto skolas kavējumu iemesli Dubnas pagasta pašvaldībā un izstrādāta sociālpedagoģiska darbības programma ģimenēm skolēnu neattaisnoto kavējumu novēršanā. Izstrādātās programmas aprobācijas analīze liecina, ka savlaicīgi konstatēti problēmas cēloņi un pārdomāta sociālpedagoģiska darbība ģimenē, veicina pozitīvu darba rezultātu neattaisnoto skolas kavējumu novēršanā. Atslēgvārdi: skolēns, ģimene, vecāki, sociālpedagoģiskā darbība, pašvaldība.

The diploma paper „Social pedagogical activities in the local municipality of Dubna small rural district for decreasing unjustified non-atendance” raises a socially significant problem. The objective of the diploma paper is to characterize social pedagogical activity in the local authority of Dubna rural district and work out a programme for decreasing unjustified non-attendance, substantiate it theoretically and analyze the results of approbation of the programme. In the diploma paper the role of family, school and society for decreasing unjustified non-atendance has been examined, as well as considered possibilities of the rural municipality to favour advancement. In the practical part of the diploma paper, basing on the research, causes of unjustified non-attendance in the local authority of Dubna rural distict are analysed and social pedagogical activity programme for families is developed for eliminating unjustified non-atendance. The analysis of the approbation of the developed programme testifies that duly established causes of the problem and deliberative social pedagogical activity facilitates a positive result of work in decreasing unjustified non-atendance. Key words: pupil, family, parents, social pedagogical activity, local authority
Social pedagogical activities in the local municipality of Dubna small rural district for decreasing unjustified non-atendance
Keywords: Pedagoģija